A new deep-water Astyris species (Buccinoidea: Columbellidae) from the southeastern Pacific - Araya, Juan Francisco; Catalán, Ricardo; Aliaga, Juan Antonio (Zootaxa, 2016)
Marine mollusks from northern Chile and from the Región de Atacama in particular have been sparsely documented, and only a few works have reviewed the area (see Araya & Araya, 2015; Labrín et al. 2015; Araya & Valdés 2016). Mollusks from deep water and offshore areas are one of the least known groups and, apart from some classic works from the 19th century, only McLean (1970), Bernard (1983), Véliz and Vásquez (2000), Fraussen & Haddorn (2000), Houart (2003), Vilvens & Sellanes (2010), and Araya (2013) have included deep-water molluscan species from northern Chile. Among the Neogastropoda, the Columbellidae constitute a quite diverse and well-distributed family of small snails, with about seven hundred extant species distributed in 70 genera (deMaintenon, 2014). Most columbellids are active epibenthic carnivores or scavengers; their shells are small, normally between 3 and 20 mm in height and they can have determinate growth, with many adult shells presenting a thickened outer lip with denticles on the interior surface (Squires, 2015). In the southeastern Pacific off Chile this family is represented by only 14 species, all from shallow water, mostly found in the northern and central parts of the country (Valdovinos, 1999).